The Protection of Land Rights in Ethiopia - Witten, Montgomery Wray (Afrika Focus, 2007)
Protection of land rights takes place within a complex interconnected environment of constantly changing domestic institutions and organizations at the federal, state and local levels of society. Usually these institutions and organizations function imperfectly, are the subject of a variety of ongoing reforms, and are poorly understood by those who seek to change them. These statements are as true of rich countries as of poor, but poverty does matter. This paper frames the Ethiopian environment within an Ecology of Land Rights Protection, presents examples of the current mixture of outcomes, and concludes with observations about the work of the Mekelle University Law Faculty in improving human rights protection. Key Words: Land Rights, Federal Laws and Regional Laws, Tigray, Land Registration and Certification, Local Government